KEBIJAKAN PEMERINTAH TENTANG UAN DALAM PERSPEKTIF OTONOMI DAERAH - Naimah, Naimah (Pascasarjana UIN ANTASARI Banjarmasin, 2008)
National Exam, as a government policy to incrcase the quality of graduales' education in lndonesia has been started since academic year 2002/2003. This policy produces many pros and cons in the society and results in under passing grade students. This is due to different levels educational quality in each region. ln the matter ofjuridisprudence, this national exam policy actually is not in line witl'r the Act no 22 year 1999 about regional sutonomy. The Act states that education matter is a part of regional autonomy so that a region has rights to participate in conducting its education in accordance with its regional potential. 'fo observe this government policy on National Exam, the writer in this paper ernploys two theories; constitrutional and systemic.